The short and long-term performance of terminated merger and acquisition deals listed on the Johannesburg stock exchange - Ward, Bradyn (My University, 2022)
This study examines the short and long-term performance of companies that experienced terminated Merger and Acquisition (M&A) deals on the Johannesburg Stock Exchange (JSE). The empirical evaluation is conducted over a 24-year period, from 1997 to 2020. It develops short and long-term testable hypotheses for the JSE-listed companies. In the short-term, the standard event study methodology is used to evaluate if there is wealth creation for the acquiring shareholders after the announcement and termination announcement of the M&A deal. The results indicate that the M&A announcement created wealth for shareholders over the sampled period whereas the termination announcement did not. Furthermore, when the sample was split, there was a significant amount of wealth created for the announcements during the 2009 to 2020 period whereas the announcements depleted shareholder value for the period spanning from 1997 to 2008. In the long-term, the performance of companies that experienced terminated and completed M&A deals is assessed by evaluating the operating performance using accounting measures. The results suggest that not participating in M&As is more beneficial to companies as they perform at a higher level than companies that completed M&A deals. Moreover, this study demonstrates that the different deal characteristics that would have been used in the completion of the M&A deal contribute to the acquiring companies’ long-term performance.
A research report submitted in partial fulfilment of the Degree of Master of Commerce in Finance to the Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2022